Key Human-Centered Transition Issues for Future Oceanic Air Traffic Control Systems - Major, Laura; Johannsson, Hlynur; Davison, Hayley; Hvannberg, Ebba Thora; Hansman, R. John (2004)
Communication, navigation, surveillance, and decision support capabilities in Oceanic air traffic control are evolving significantly. It is important to consider the effect of the changes on the controller’s task. In this paper the results from multi-disciplinary studies performed at MIT (Massachusetts Institute of Technology) and the University of Iceland are presented. At MIT, a human-centered systems analysis was used to identify key human factors issues for the future Oceanic air traffic control environment to be experimentally investigated. At the University of Iceland, a prototype for a future air traffic control display was designed and evaluated. Both studies identified three key human factors issues that require consideration. The first is a mismatch between time and space separation restrictions imposed and information support provided, requiring the controller to cognitively resolve temporal/spatial mismatches to meet restrictions. The second issue is the effects of mixed communication and surveillance equipage, which complicates the control task and requires the controller to cognitively integrate asynchronous information. The final is the importance of cultivating controller trust and understanding issues of complacency and automation disuse when implementing highly automated conflict probes that are being considered in the future Oceanic environments.